Welfare and Macroeconomic Interdependence - Corsetti, G.; Pesenti, P. (Quarterly Journal of Economics, 2001)
We develop a baseline model of monetary and fiscal transmission in interdependent economies. The welfare effects of expansionary policies are related to monopolistic supply in production and monopoly power of a country in trade. An unanticipated exchange rate depreciation can be beggar-thyself rather than beggar-thy-neighbor, as gains in domestic output are offset by deteriorating terms of trade. Smaller and more open economies are more prone to suffer from inflationary shocks. Larger economies benefit from moderate demand-led expansions, but may be worse off if policy-makers attempt to close the output gap. Fiscal shocks are generally beggar-thy-neighbor in the long run; in the short run they raise domestic demand at given terms of trade, thus reducing the welfare benefits from monetary expansions. Analytical tractability makes our model uniquely suitable as a starting point to approach the recent “new open-economy macroeconomic” literature.